SISTEM INFORMASI PENDAFTARAN SERTIFIKASI TANAH BERBASIS WEB DI KANTOR BADAN PERTANAHAN NASIONAL KOTA LANGSA - Arief Maulana; Nurul Fadillah; Mudhi Ulfani (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2020)
Land is a valuable asset. In addition, land is a vital need for anyone because it can be used in various fields, including agriculture, settlement, trade, industry and mining. The increase in population each year is not proportional to the increase in land area, it allows everyone to try to own and control land. In line with the need for land, it is necessary to increase the handling of land administration by designing and creating a land certification registration information system to assist the land certification process at the Langsa City Land Agency Office. The land certification information system consists of several features that are differentiated according to access rights, namely user and admin. The design of the system to be created, as well as the database design on this system, uses ERD to determine the relationships between tables. This information system was created as a medium for land certification registration at the Langsa City Land Agency Office.